2009
DOI: 10.1590/s0103-84782009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilidade de Metarhizium anisopliae à temperatura e umidade em três tipos de solos

Abstract: III RESUMO Este trabalho teve como objetivo investigar o efeito da temperatura e do teor de umidade do solo na sobrevivência de Metarhizium anisopliae (Metsch.) Sorok. em três tipos de solos. Foram utilizados o Latossolo Vermelho textura argilosa, Latossolo Vermelho textura média e Argissolo Vermelho zero, 20, 40, 60, 80, 100 e 120 dias de incubação em cada temperatura estudada. Na análise do efeito do teor de umidade, a sobrevivência foi avaliada após zero, 14, 28, 42, 56, 70, 84, 98

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…This observation tends to counter the more typical hypothesis that younger/smaller immature insects are more susceptible to biological control agents (Yokoyama et al 1998). Our experiments did not directly evaluate this hypothesis because numerous environmental factors likely influenced fungal growth (Lanza et al 2009, Garrido-Jurado et al 2011) and subsequent levels of larval exposures to the fungus in field plots. Improved control of larger larvae, as we observed, may be a result of favorable environmental conditions (soil temperatures and/or availability of moisture) for the late season application that supports growth and survival of the fungus.…”
Section: Discussionmentioning
confidence: 76%
“…This observation tends to counter the more typical hypothesis that younger/smaller immature insects are more susceptible to biological control agents (Yokoyama et al 1998). Our experiments did not directly evaluate this hypothesis because numerous environmental factors likely influenced fungal growth (Lanza et al 2009, Garrido-Jurado et al 2011) and subsequent levels of larval exposures to the fungus in field plots. Improved control of larger larvae, as we observed, may be a result of favorable environmental conditions (soil temperatures and/or availability of moisture) for the late season application that supports growth and survival of the fungus.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, Gaugler et al (1989) found that a high level of Colorado potato beetle (Leptinotarsa decemlineata, Say) mycosis only occurred after soil irrigation. However, studies on the impact of soil moisture on conidia viability and mycosis have produced contradictory results (Lingg & Donaldson, 1981;Studdert & Kaya, 1990;Hallsworth & Magan, 1995;Lanza et al, 2009;Cossentine et al, 2010). Studdert and Kaya (1990) showed a significant increase in Spodoptera exigua (Hübner) pupal mycosis by B. bassiana (strain ABG 6178) at water potentials of -37 to -200 bar compared with -0.3 to -15 bar.…”
Section: Apple Sawfly Mortality In Fieldmentioning
confidence: 99%
“…al., 2001Baratto, 2005). A temperatura ótima de cultivo do fungo Metarhizium anisopliae é de 28°C (Dortas e Arcas, 1998;Pollar, 2005 exposto a temperaturas acima e abaixo de suas condições ótimas tem sua esporulação reduzida (Keyser et al 2014, Lanza et al, 2009). …”
Section: Introductionunclassified